Essential role of Mia40 in import and assembly of mitochondrial intermembrane space proteins - Chacinska, Agnieszka (Nature Publishing Group, 2004)
Mitochondria import nuclear-encoded precursor proteins to four different subcompartments. Specific import machineries have been identified that direct the precursor proteins to the mitochondrial outer membrane, inner membrane or matrix, respectively. However, a machinery dedicated to the import of mitochondrial intermembrane space (IMS) proteins has not been found so far. We have identified the essential IMS protein Mia40 (encoded by the Saccharomyces cerevisiae open reading frame YKL195w). Mitochondria with a mutant form of Mia40 are selectively inhibited in the import of several small IMS proteins, including the essential proteins Tim9 and Tim10. The import of proteins to the other mitochondrial subcompartments does not depend on functional Mia40. The binding of small Tim proteins to Mia40 is crucial for their transport across the outer membrane and represents an initial step in their assembly into IMS complexes. We conclude that Mia40 is a central component of the protein import and assembly machinery of the mitochondrial IMS.